Synthesis of Water‐Dispersible Boron Nitride Nanoparticles. Issue 19 (27th May 2014) - Xiong, Chengjia; Tu, Weixia
Abstract: Spherical boron nitride nanoparticles with good aqueous dispersibility were synthesized by means of a direct reaction of boric acid and ammonium chloride. The X‐ray powder diffraction pattern confirmed the hexagonal BN structure ( h‐ BN) with d 002 = 3.33 Å. Copper oxide (CuO) was found to affect the morphology and surface properties of the BN nanoparticles. The average size of the spherical h ‐BN nanoparticles synthesized with the addition of CuO was about 30 nm. The h ‐BN had a high surface area of 75 m 2 g –1 and a mesoporous volume of 0.32 cm 3 g –1 . The presence of CuO during the synthesis could enhance the surface electronegativity of the h ‐BN nanoparticles and change their isoelectric point to pH = 2.7. The zeta potentials of BN were between –30 and –50 mV in the pH range of 4–10. The h ‐BN nanoparticles were well dispersed and stable in aqueous solution. Abstract : Small‐sized hexagonal boron nitride ( h ‐BN) nanoparticles have been synthesized. Copper oxide plays a role in changing the surface properties of h ‐BN nanoparticles and improving their aqueous dispersibility. The h ‐BN nanoparticles can be well dispersed and are stable in aqueous solution.